NULLUM CRIMEN NULLA POENA SINE LEGE PRINCIPLE AND THE ICTY AND ICTR - Endo, Guillaume (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2002)
Not many scholarly writings deal with sentencing practices of the ICTY and the ICTR. When compared to frequently discussed topics within the subject matter jurisdiction of the ad hoc Tribunals, they are relatively scarce. Both of these Tribunals’ Statutes provide a sentencing regime encompassing, inter alia, a reference to national sentencing practice. It is the author’s view that the provisions of the statutes and rules of procedure and evidence may violate the nullum crimen nulla poena sine lege principle in certain respects. Without a doubt, the rationale underlying the Second World War precedents with respect to sentencing does not accurately reflect the status of international law norms today. As such, the evolvement of human rights law must be reflected in the current sentencing practice of the ad hoc Tribunals. Moreover, the ICTY and ICTR interpretation of the international sentencing mechanism provides inconsistent justice, which in turn harms the legacy of these ad hoc Tribunals. In fact, an accused could successfully argue that life imprisonment as provided by rules 101 of the Rules of Procedure and Evidence of both ICTY and ICTR are not prescribed by law. Accordingly, the ICTY and ICTR provisions regarding sentencing should be amended.